A new species of Rhacophorus (Anura: Rhacophoridae) from Guangxi Province, China - Rao, Ding-Qi; Wilkinson, Jeffery A.; Liu, Hui-Ning (Zootaxa, 2006)
A new species of Rhacophorus is described from Guangxi Province, China. The new species, Rhacophorus minimus, is the smallest of the known green species of Rhacophorus, with a SVL averaging only 28.1 mm for males and 37.0 mm for females. Other characters that separate it from other green Rhacophorus species include a smooth bright green dorsum, lacking tubercles and pattern; a white stripe from tip of snout along the upper lip and shoulder to insertion of hind limbs; reduced webbing, less than a third of the length of outer fingers; and disc of the 3rd finger smaller than the diameter of the tympanum.